OVERURBANIZATION IN SEMARANG CITY - Wilonoyudho, Saratri (Semarang State University, 2011)
The economic growth in Semarang has resulted in bad impact of degradation the environment, traffic jams, increasing informal sectors and unemployment, crimes, and various social-politic conflicts. From this phenomenon, it is suspected that Semarang is undergoing overurbanization, that is the imbalance between population and economic growth.Â Â Â Â Â Â Â Â Â Â From the result of research, it can be concluded that the main determinant of urbanization process in Semarang is the prolonged capitalization from colonial era. However, it not industrialization that develops, but informal sectors and service sectors. The impact is the city involution because as if the new employees can never participate in informal sectors. As a result, the Semarang City Government must mobilize non-producing resources to finance creating and organizing the needed service for high concentration of population under low standard of industrialization. In other words, Semarang and the hinterland are indeed undergoing âde-industrializationâ. Industrial and agricultural sectors decreases their role, and on the other hand the service sector increases. In those areas, urbanization tends to occur with a spreading pattern characterized by high rate of population in urban areas like in regencies surrounding Semarang. The economic growth in those areas does not depend on the core city, Semarang, so that the level of advanced primate city has been passed through. The suggestions proposed are that the megapolitan issues has been reached, thus the things that need to consider in megaregional tendency. The regencies in the hinterland are proven âto balanceâ the global capitalism, apart from wether the growth of enterpreunership innovation is accompanied by significant increase of welfare. This means that things need further attention is to manage the relationship between locality and production system and global economic in those ares to make people welfare and prevent people to migrate to other big cities.Â